Time to revisit the enigma of mastalgia management - Singh, Arun Kumar; Kuraria, Vaibhav; Mohit,; Khera, Dhananjay; Saini, Yogesh; Raju, Hinduja (International Surgery Journal, 2024)
Mastalgia (breast pain) also known as mastodynia, is one of the most common causes of breast issues for which a female visits a medical practitioner. It is divided into cyclical mastalgia, which is associated with menstruation, or can be noncyclical mastalgia which can present premenopausal or postmenopausal. The incidence of breast cancer associated with mastalgia is extremely low and reassurance plays a major role in the treatment of patients. Hormonal changes have been associated with the pathogenesis of cyclical mastalgia. Outdated treatment modalities are still being followed even though newer and more effective treatment options have been established. Objective assessment of breast pain should be done with the visual analog scale. Non-pharmacological therapy should be encouraged in every patient of mastalgia such as counseling and reassurance, sports bra, yoga, and relaxation therapy. Tamoxifen and ormeloxifene are now the drug of choice in severe mastalgia and care should be taken to counsel the patients about use and common and detrimental side effects. The available treatment modalities and their directions to use are discussed in this review.